Uneven Development Principles in Geo-Map Perspective: How Does Infrastructure Play a Role in Crushing the Poverty in the Special Region of Yogyakarta? - Ratnadewati, Ainina; Samudro, Bhimo Rizky; Widiastuti, Nur; Popoola, Oluwatoyin Muse Johnson (Muhammadiyah University Press, 2024)
The purpose of this study is to determine the relationship between the existence of regional infrastructure and the number of poor people and to know the distribution of infrastructure in each district/city in the Special Region of Yogyakarta (DIY). The data used is a primary data crosssection derived from Village Potential Data Collection (Q-Podes). This study uses two methods, namely, Ordinary Least Square Regression, to determine the relationship between variables and Geo-Map Orange Data Mining to determine the distribution and equitable distribution of infrastructure. Empirical results show that areas with electricity sources from the State Electricity Company (PLN), Information and communication infrastructure, trade and service infrastructure, agricultural infrastructure, and good sanitation can reduce the number of poor people. However, drainage infrastructure, cultural and health education infrastructure, and transportation infrastructure have not been able to reduce the number of poor people in DIY. In addition, the occurrence of uneven development, which is seen in the uneven infrastructure in each region, is also an inhibiting factor in reducing the number of poor people in DIY.